2017
DOI: 10.1080/01612840.2017.1378783
|View full text |Cite
|
Sign up to set email alerts
|

Testing Nursing Sensitive Outcomes in Out-Patient Drug Addicts, with “Nursing Role Effectiveness Model”

Abstract: Our aim was to identify factors that contribute to a better outcome in drug users and to understand the effectiveness of nursing interventions, by applying "Nursing Role Effectiveness Model" (NREM). It's a correlational, cross-sectional study with 180 drug users in a methadone program, randomly selected from three community services. We identified that treatment time, lower co-morbidities, less poly-drug use, family support and being employed contribute to a better quality of life, better mental health, less s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 24 publications
0
29
0
5
Order By: Relevance
“… 1 Doran et al (); 2 Doran et al (); 3 Doran et al (); 4 Endacott et al (); 5 Gazarian, Moineddin, and Agha (); 6 Kossman and Scheidenhelm (); 7 Manojlovich (); 8 Manojlovich et al (); 9 Salgueiro et al (); 10 Saunders (); 11 White et al (); 12 Doran et al (); 13 Landesman et al (); 14 Rondinelli et al, ; 15 Tarlier (); 16 Seabra et al (). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Doran et al (); 2 Doran et al (); 3 Doran et al (); 4 Endacott et al (); 5 Gazarian, Moineddin, and Agha (); 6 Kossman and Scheidenhelm (); 7 Manojlovich (); 8 Manojlovich et al (); 9 Salgueiro et al (); 10 Saunders (); 11 White et al (); 12 Doran et al (); 13 Landesman et al (); 14 Rondinelli et al, ; 15 Tarlier (); 16 Seabra et al (). …”
Section: Resultsmentioning
confidence: 99%
“…The second article that used the NREM in ambulatory care was completed by Seabra, Amendoeira, and Sà (). Specifically, they examined the NREM in the context of an outpatient drug unit for patients with a methadone addiction to determine how effective nursing interventions are in relation to the patient outcomes when treating patients with substance addictive behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants stated that, in detriment of the referral for the patients to the ECCI, they were referred to the inpatient services of the RNCCI network, due to the fact that the patients need continuous care and the ECCI schedules are not adequate to their real needs, such as elucidated in the excerpts of the interviews: (results) (16,27) .…”
Section: Referral Processmentioning
confidence: 99%
“…A number of studies carried out in the context of outpatient care have shown that nursing interventions have contributed to improving the results of the patients (27) . NREM has the potential to identify specific results generated by the care provided by nurses, highlighting the role and responsibility of the Nursing profession, and justifying its importance in making decisions about health policies (16) .…”
Section: Referral Processmentioning
confidence: 99%